An overview of mallet finger injuries - Khera, Bhavika; Chang, Chad; Bhat, Waseem (Acta Biomedica Atenei Parmensis, 2021)
Mallet finger describes a fingertip deformity where the distal interphalangeal joint (DIPJ) of the affected digit is held in flexion, unable to extend the distal phalanx actively. The deformity is typically a consequence of traumatic disruption to the terminal extensor tendon at its insertion at the proximal portion of the distal phalanx or slightly proximally at the level of the DIPJ. Patients typically present with a history describing the event of injury with a typical mallet deformity. Common mechanisms include sport activities causing a direct blow to the finger, low energy trauma while performing simple tasks such as pulling up socks or crush injuries from getting the finger trapped in a door. The DIPJ can be passively extended, but this extension of the joint cannot be maintained once the passive extension is stopped. The Doyle classification can be used to categorise and dictate treatment. The extensor lag associated with the deformity does not improve spontaneously without treatment. Inappropriate management can lead to chronic functional loss and stiffness of the finger. The majority of closed mallet splints are Doyle type I, which can be managed non-surgically with external splints, worn full-time to keep the fingertip straight until the tendon injury or fracture heals. Surgical techniques is considered for other types of mallet injuries. Techniques used include closed reduction and Kirschner wire fixation, open reduction and internal fixation, reconstruction of the terminal extensor tendon and correction of swan neck deformity.